2020
DOI: 10.3390/coatings10080740
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer-Structured Wood Electroless Cu–Ni Composite Coatings for Electromagnetic Interference Shielding

Abstract: The lightweight multilayer-structured electromagnetic interference shielding composite coatings with controllable electromagnetic gradient on wood surface were prepared via a simple multiple electroless copper–nickel (Cu–Ni) approach. The surface morphology, conductivity, hydrophobicity property and electromagnetic shielding effectiveness of the composite coatings were investigated. The surface roughness and conductivity of the composite coatings were enhanced with the increase in the number of depositions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In general, shielding effectiveness increases with thickness. Therefore, we utilize the normalized EMI SE/thickness to compare the shielding properties of AN@MX/TW composites and other reported wood-based composites. , As shown in Figure c, the AN@MX/TW composite with a thickness of about 1 mm reaches a maximum normalized SE/thickness of 44.96 dB/mm, which is much higher than most other reported values. The conductivity of AN@MX/TW composite can induce electrical heating with fast thermal response time (∼40 s for heating process and ∼60 s for cooling process) in Figure d,e.…”
Section: Resultsmentioning
confidence: 96%
“…In general, shielding effectiveness increases with thickness. Therefore, we utilize the normalized EMI SE/thickness to compare the shielding properties of AN@MX/TW composites and other reported wood-based composites. , As shown in Figure c, the AN@MX/TW composite with a thickness of about 1 mm reaches a maximum normalized SE/thickness of 44.96 dB/mm, which is much higher than most other reported values. The conductivity of AN@MX/TW composite can induce electrical heating with fast thermal response time (∼40 s for heating process and ∼60 s for cooling process) in Figure d,e.…”
Section: Resultsmentioning
confidence: 96%
“…They found that the disks' resistance would decrease from 12 Ω to 1 Ω within the first 5 minutes of electroless plating, that the hydrophobicity of the coated wood slightly increased, and that an electromagnetic shielding effectiveness between 55 Db and 65 Db could be achieved. Similar methods were also studied to coat poplar with Cu-Ni [168] and Ni-P [169] composites. A superhydrophobic wood surface was created by Wang et al by deposing copper on a wood substrate with a vacuum evaporator, followed by the growth of a silver layer through immersion in a AgNO 3 solution [170].…”
Section: Inorganic Coatingsmentioning
confidence: 99%
“…EM shielding materials are attracting great attention due to their specific function in overcoming EM interference (EMI) problems and are in demand for medical, aerospace, and military applications [2]. Many materials have been explored as EM shielding materials [3][4][5], and among them, EM shielding fabric is an important new kind of material or product for EM shielding because of its softness, breathability, and easy machining [6].…”
Section: Introductionmentioning
confidence: 99%